Continuity and change : gestalt therapy now : the 10th biennial conference of the Association for the Advancement of Gestalt Therapy /: gestalt therapy now : the 10th biennial conference of the Association for the Advancement of Gestalt Therapy. (2011) - Unknown
No abstract available